Possible Central Nervous System Infection by SARS Coronavirus - Kwok-Kwong Lau; Wai-Cho Yu; Chung-Ming Chu; Suet-Ting Lau; Bun Sheng; K.Y. Yuen (Emerging Infectious Diseases, 2004)
On day 22 of illness, generalized tonic-clonic convulsion developed in a 32-year-old woman with severe acute respiratory syndrome (SARS). Cerebrospinal fluid tested positive for SARS coronavirus (SARS-CoV) by reverse transcriptase–polymerase chain reaction. SARS-CoV may have caused an infection in the central nervous system in this patient.